Contrast-enhanced ultrasound in coxitis - Löffler, Christian; Sattler, Horst; Uppenkamp, Michael; Bergner, Raoul (Joint bone spine, 2016)
Objectives - Hip involvement is common in rheumatological diseases but can be difficult to diagnose, especially in absence of MRI. B-mode ultrasound (US) detects joint capsule distention while distinguishing effusion from proliferative synovial tissue is strenuous since both appear hypoechoic. Power Doppler ultrasound (PDUS) often fails to detect vascularisation in the hip. We therefore evaluated contrast-enhanced ultrasound (CEUS) in the hip joint. - Methods - We investigated 36 hip joints of patients with known rheumatological joint diseases presenting with hip pain and 5 hips of healthy controls using B-mode US, PDUS and CEUS. We assessed CEUS hypervascularisation semiquantitatively comparing to the periarticular tissue. In B-mode, we measured the distance between femoral neck and joint capsule (DNC) and compared the results to the avascular intraarticular margin (AIM) in CEUS using t-tests and crosstables. - Results - PDUS signals were received in only 2/36 cases (5.6%). B-mode US established the diagnosis of coxitis in 64% of all symptomatic hip joints. In 4 cases (11%), the diagnosis was revised after the use of CEUS. In patients with definite coxitis, 14 hips (73.7%) showed CEUS hypervascularisation°2, five°1 (26.3%) and none°0 (χ2=3.277, P<0.001). The difference DNC/AIM was highly significant in patients with hip pain (P<0.001, 95% CI: 2.054-4.684) and those with definite coxitis (P<0.001, 95% CI: 3.268-7.258). - Conclusions - In most cases, clinical parameters together with B-mode US findings are sufficient to diagnose coxitis. However, CEUS is capable of visualizing and quantifying the degree of hypervascularisation and enables the discrimination between effusion and proliferative synovial tissue.
Gesehen am 28.03.2019
Available online 7 April 2016